SCIENCE, EDUCATION & COGNITIVE COMPETENCE BASED ON E-LEARNING - Kassymova K. Gulzhaina; Arpentieva R. Mariam; Kosherbayeva N. Aigerim; Triyono B. Mochamad; Sangilbayev S. Ospan; Kenzhaliyev K. Bagdaulet (Scientific Journal of Pedagogy and Economics, 2019)
This article is devoted to the development of the educational process, including in the context of ideas about digital learning. Although in recent years, electronic learning has often become the object of research and practical development, many practitioners and theorists do not fully understand what the concept of “e-learning” really means, does not understand how it can help teachers and educators to achieve success in students’ knowledge. The authors of the article consider the historical foundations of digital education and the use of information technologies in education. They believe that the leading changes in education associated with digital learning are that digital learning develops the cognitive competence of schoolchildren and students. Using the example of learning foreign languages, the article shows that the use of e-learning stimulates the development of metacognitive components of cognitive competence, and also activates the declarative and procedural components of cognitive activity